The Effect Arm Muscle Explosive Power and Self Confidence to Speed Of Service - Indri Wulandari; Muhammad Arnando; Rices Jatra; Andre Igo Resky (Pusat Kajian Pendidikan Olahraga, Kesehatan, dan Rekreasi Jurusan Pendidikan Olahraga Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2021)
Analysys path study aims to obtain information about the effects explosive power arm muscles and self confidence to speed of service. This study was conducted to athletes Tennis Club Padang. The population number of 42 people, samples were taken by purposive sampling technique. Samples of this research are 30 male tennis athletes. The hypothesis testing explosive power arm muscles directly affect the speed of service 0.1592. Self Confident directly affect the speed of service 0.1211. Explosive power arm muscles directly affected to confidently 0.4303. The study concluded: 1) Explosive power arm muscles directly affect the Speed of service. Self Confident directly affect the Speed of service (2). Explosive power arm muscles directly affect to self-confidence (3).